The Interplay of Inflammatory Processes and Cognition in Alcohol Use Disorders—A Systematic Review - Coppens, Violette; Morrens, Manuel; Destoop, Marianne; Dom, Geert (Frontiers in Psychiatry, 2019)
Rationale Of late, evidence emerges that the pathophysiology of psychiatric diseases and their affiliated symptomatologies are at least partly contributable to inflammatory processes. Also in alcohol use disorders (AUD), this interaction is strongly apparent, with severely immunogenic liver cirrhosis being one of the most critical sequelae of chronic abusive drinking. This somatic immune system activation negatively impacts brain functioning and additionally, alcohol abuse appears to have a direct detrimental effect on the brain by actively stimulating its immune cells and responses. As cognitive decline majorly contributes to AUD’s debility, it is important to know to what extent impairment of cognitive functioning is due to these (neuro-)inflammatory aberrations. Method We hereby summarize the current existing literature on the interplay between alcohol use disorders, inflammation and cognition in a systematic review according to the PRISMA-P guidelines for the systematic review. Main findings Although literature on the role of inflammation in alcohol use-related cognitive deficiency remains scarce, current findings indicate that pro-inflammatory processes indeed result in exacerbation of several domains of cognitive deterioration. Interestingly, microglia, the immune cells of the brain, appear to exert initial compensatory neuroprotective functionalities upon acute ethanol exposure while chronic alcohol intake seems to attenuate these responses and overall microglial activity. Conclusion As these results indicate inflammation to be of importance in cognitive impairment following alcohol consumption and might as such provide alternate therapeutic avenues, a considerable increase in research efforts in this domain is urgently required.